Variable-rate applications of soil-applied herbicides in corn and grain sorghum - Gundy, Garrison James (Kansas State University, 2018)
Field experiments were conducted in 2016 and 2017 across nine locations in Kansas to develop and evaluate a procedure for variable-rate applications (VRA) of soil-applied herbicides in corn and grain sorghum based on soil properties. Soil electrical conductivity (EC) and soil organic matter (SOM) data were collected at each location using a Veris MSP3. Soil EC was correlated to soil texture and herbicide algorithms were developed for two different tank-mixes for corn and for grain sorghum. Three algorithms were evaluated in the field for each tank-mix based only on SOM (alg-SOM), SOM and soil texture (alg-SOMtex), or a flat rate based on the average soil properties for the entire field. Rates for each tank-mix were based on the maximum usage rate (MUR) allowed. When soil variability across a field was adequate, VRA based on algorithms were effective at five of the nine locations. Across these five locations, alg-SOM resulted in the same or better weed control at 8 weeks after treatment (WAT) compared to the flat rate and reduced herbicide use by 12% for both tank-mixes in grain sorghum. Using alg-SOMtex reduced herbicide use by 24% in grain sorghum, but had less weed control at several locations compared to the flat rate. VRA was practical at Morganville, KS in 2017. Both alg-SOM and alg-SOMtex increased the amount of herbicide applied compared to the flat rate, but alg-SOMtex resulted in greater Palmer amaranth control (92%) compared to the flat rate (71%). Separate greenhouse and field experiments were conducted in 2017 to evaluate the activity of soil-applied herbicides on controlling HPPD-inhibitor resistant Palmer amaranth populations. A dose-response greenhouse experiment of soil-applied mesotrione and isoxaflutole was performed using resistant (Stafford County) and susceptible (Riley County) Palmer amaranth populations. Reduced susceptibility was observed with resistant-to-susceptible ratios being 7.2 for mesotrione and 4.1 for isoxaflutole. Field experiments were conducted at two locations in KS with one field having HPPD-resistant (Barton County) and the other HPPD-susceptible (Reno County) Palmer amaranth populations. Treatments were three HPPD-inhibiting herbicides [mesotrione (¼X, ½X, and 1X = 210 g ha⁻¹), isoxaflutole (½X and 1X = 105 g ha⁻¹), and bicyclopyrone (1X = 50 g ha-1 and 2X in formulated tank-mix with bromoxynil at 700 and 1400 g ha-1)] in comparison to other soil-applied herbicides commonly used for Palmer amaranth control. HPPD-inhibitor treatments were applied alone and tank-mixed with atrazine (2240 g ha⁻¹). Overall, control of Palmer amaranth was reduced for HPPD-resistant compared to -susceptible populations. All treatments of mesotrione and isoxaflutole at 4 WAT resulted in 81 to 99% control in Reno County, but only 55 to 89% control in Barton County. For mesotrione and isoxaflutole treatments across both sites, Palmer amaranth control at 4 WAT was greater when 1X was applied (89%) compared to 0.5X (81%). Tank-mixing atrazine with mesotrione and isoxaflutole increased Palmer amaranth control from 82 to 88%. Soil-applied HPPD-inhibitors were most effective when applied at field usage rate in combination with atrazine for both populations. When using soil-applied HPPD-inhibitors, management recommendations should be the same regardless of Palmer amaranth population.
Keywords: Soil-applied herbicide; Palmer amranth; HPPD-inhibitor; Variable-rate application; Soil organic matter; Preemergence